INSIGHTS FROM THE MIDDLE OF NOWHERE: PROVERBIAL LANGUAGE AND INTERTEXTUALITY IN GARY LARSON’S THE FAR SIDE - Winick, Stephen D. (Proverbium - Yearbook, 2014)
This paper examines proverbs in the work of the popular cartoonist Gary Larson, creator of the daily panel The Far Side. It looks particularly at Larson’s use of the literalized metaphor as a way to suggest reversed hierarchies and thus open the way for social criticism. In this way, it suggests a connection between Larson’s work and the centuries-old tradition of World Upside-Down art, which also featured literalized proverbs. It recognizes, however, that such cartoons fre-quently inhabit the border between sense and nonsense, making out-right social criticism less likely than a general lampooning of social norms and ideals. Through close analysis of many Far Side cartoons, it reveals many of Larson’s intertextual strategies, and concludes that Larson is arguably one of the greatest proverb illustrators of all time. An index of proverbs and proverbial phrases in The Far Side is included.